Africa in the Bengali imagination : from Calcutta to Kampala, 1928-1973 - Mowtushi, Mahruba T. (Abingdon, Oxon ; New York : Routledge, Taylor & Francis Group, 2025)
"This book examines textual representations of Africa in the Indian imagination from 1928 to 1973. It critically analyses Bengali literature during this period, their imitation of colonial racial prejudices and how it allowed Bengalis to fashion their identity. It analyses the development of 'Africa' as an idea and historical reality through the writings of five Bengali writers including, the Bengali novelist Bibhutibhusan Bandapadhyay, the children's author Hemendrakumar Roy, the poet and philosopher Rabindranath Tagore, the playwright Ganesh Bagchi and the surrealist poet and founding editor of Transition magazine Rajat Neogy. The book shows how these writers engage with the idea of Africa and their influence in the construction of the Bengali cultural identity during the freedom struggle, the Partition of Bengal in 1947 and the creation of Bangladesh in 1971. The book offers readers a glimpse of the exotic imaginary locales of Africa while offering an in-depth look into the interconnected histories, cartographic routes and cultural exchange between India and Africa. A first of its kind, this book will be an excellent read for students and scholars of literature, comparative literature, history, cultural studies, post-colonial studies, South Asian studies, African studies and diaspora studies"--
Introduction -- The Replenishment of Bengal: Bibhutibhusan Bandyopadhyay's African Adventure Novel, Chander Pahar (1933) -- Space, Place and the Body: The Nationalist Bhadrolok in Hemendrakumar Roy's African Story, Abar Jakher Dhan (1933) -- 'A Call to Duty': Rabindranath Tagore on Africa -- Ganesh Bagchi and the Narratives of Longing and Belonging in Uganda, 1948-1964 -- Nations and nationalities in Transition: The Poems of Rajat Neogy for Transition Magazine, 1962-1973 -- Conclusion.
Includes bibliographical references and index.
ENH
Keywords: Bengali literature -- 20th century -- History and criticism; Bengali (South Asian people) -- Africa; Africa -- In literature